PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS DAN KINERJA PASAR PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI PADA PERIODE 2014-2020 - Neni Hendayani; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2022)
Good Corporate Governance (GCG) is something that is considered important in an organization or company. Companies that pay attention to a good governance system are proven to be able to continuously improve their company performance. The purpose of this study is to determine and provide empirical evidence regarding the effect of good corporate governance (GCG) on profitability and market performance. Good Corporate Governance (GCG) in this study is proxied by institutional ownership, managerial ownership, board of directors, independent commissioners, and audit committee. Profitability in this study is proxied by ROE (Return On Equity) and market performance is proxied by tobins'q. The population in this study are insurance companies listed on the Indonesia Stock Exchange for the 2014-2020 period. The sampling method in this research is using  purposive sampling which is sampling with certain predetermined criteria. The sampling method in this research is using  purposive sampling which is sampling with certain predetermined criteria.The results showed that GCG simultaneously had a significant effect on profitability and market performance.